User satisfaction on smart phone interface design, information quality evaluation - Zamzami, Ikhlas; Mahmud, Murni (2013)
Today, smart phone evolution become an important and highest competition channel through which many organisations launch and market their services to the users. Applications have delivering services by different way of attractiveness. The quality of information provided through mobile technologies is seen as one of the most critical dimensions towards organisational achievement and success. In fact, User interface designed for mobile device is the main concern in designing applications. Currently, there is few of research that particularly evaluates the quality of information on smart phone interface. In fact, the information quality has been deliver by smart phone , which is important for user convenience, has not been evaluated. In this paper, the researcher will be examined in three main areas: mobile interface design, the information quality of the applications, and whether this information has met user satisfaction.